Tariffs, productivity, and resource misallocation - Michael Kilumelume; Bruno Morando; Carol Newman; John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
An often-neglected potential negative consequence of tariffs is the impact they may have on the misallocation of factor inputs. Trade protection can provide space for domestic firms to increase prices and mark-ups, allowing low-productivity firms to survive, thereby leading to a sub-optimal allocation of resources. This paper explores the impact of tariffs on the allocation of capital using administrative data from South Africa. We find that tariffs are highly correlated with capital misallocation, leading to aggregate productivity losses of 5-10 per cent. In particular, tariffs are strongly related to distortions that are correlated with firm productivity. The main channel through which tariffs distort the allocation of capital is through the protection they offer to lowproductivity firms, reducing their probability of exiting and increasing firm survival.
Keywords: D24; F14; O12; 330; tariffs; productivity; misallocation; South Africa